Relative air temperature analysis external building on Gowa Campus. (March 2018) - Mustamin, Tayeb; Rahim, Ramli; Baharuddin,; Jamala, Nurul; Kusno, Asniawaty
Abstract: This study aims to data analyze the relative temperature and humidity of the air outside the building. Data retrieval taken from weather monitoring device (monitoring) Vaisala, RTU (Remote Terminal Unit), Which is part of the AWS (Automatic Weather Stations) Then Processing data processed and analyzed by using Microsoft Excel program in the form of graph / picture fluctuation Which shows the average value, standard deviation, maximum value, and minimum value. Results of data processing then grouped in the form: Daily, and monthly, based on time intervals every 30 minutes. The results showed Outside air temperatures in March, April, May and September 2016 Which entered in the thermal comfort zone according to SNI standard (Indonesian National Standard) only at 06.00-10.00. In late March to early April Thermal comfort zone also occurs at 15.30-18.00. The highest maximum air temperature occurred in September 2016 at 11.01-11.30 And the lowest minimum value in September 2016, time 6:00 to 6:30. The result of the next analysis shows the level of data conformity with thermal comfort zone based on SNI (Indonesian National Standard) every month.